Evaluasi Program Tahfidz di SMAN 6 Padang Menggunakan Model CIPP - Susanti, Dessi; Hidayat, M Topit; Siregar, Eva Anzani; Tullaili, Mufida; Friyatmi, Friyatmi (Universitas Negeri Padang, 2024)
This research aims to evaluate the Tahfidz program at SMAN 6 Padang. This research is included in the type of evaluation research using the CIPP (Context, Input, Process and Product) approach from Stufflebeam & Shinkfield. The instruments used for data collection in this research were interviews, observation, documentation and questionnaires conducted on students and teachers. The results of this research show that: 1) Implementation of the tahfidz program is very necessary for students and teachers to develop noble student character; 2) The quality and availability of facilities that support the Tahfidz program still need to be improved, especially in terms of the availability of libraries, technological facilities, worship facilities and sanitation; 3) The implementation of the tahfidz program has run smoothly; 4) The Tahfidz program is considered to have helped students become Hafidz or Hafidzah which has an influence on the students' character.